The histological comparison of the effect of 50mW green and blue laser on the human eye at variable time intervals: an animal model - Qamar Aqeel Shams; Ameen Mohammad Alsudani; Mustafa Salih Almusawi (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of 50mW green and blue laser pointers on retinal tissue with different exposure durations. Method: The experimental, histopathological study was conducted from November 2021 to April 2022 at the Postgraduate Laboratory of the Department of Physiology and Medical Physics, College of Medicine, Mustansiriyah University, Iraq, and comprised adult male mice. They were divided into green group G and blue group B. Group G was exposed to a 50mW green laser pointer with wavelength 532nm, while group B was exposed to a blue laser pointer with wavelength 415nm. The groups were subdivided with respect to duration of exposure. Subgroups G1 and B1 had exposure time 1min, G2 and B2 had exposure time 2min and G3 and B3 had exposure time 3min. Across the groups, the overall supplied power density was 130mW/cm2. Conventional Haemotoxylin and Eosin stain was used to assess the damage on the retinal tissues of the mice post-exposure. Data was analysed using SPSS 24. Results: Of the 24 groups, 12(50%) were in each of the 2 groups, while each subgroup had 4(16.66%) mice. There was more retinal tissue damage in group G compared to group B (p<0.05). The damage increased significantly with increase in exposure duration in both groups (p<0.05). Conclusion: The traditional green laser pointers caused more damage to the retina of mice than the blue laser. Key Words: Eosine, Retina, Lasers